Aromatic interactions in unusual backbone nitrogen-coordinated zinc peptide complexes: A crystallographic and spectroscopic study - Heinemann, Frank Wilhelm; Zahl, Achim; et al. (Inorganic Chemistry, 2005)
A series of zinc complexes with dipeptide ligands of the type Dpg-Xaa was synthesized, where Dpg is dipicolylglycine and Xaa is phenylalanine (Phe), tyrosine (Tyr), tryptophan (Trp), 2-naphthylalanine (Nal), or glycine (Gly). It was shown that aromatic interactions promote the unusual coordination of an anionic peptide backbone nitrogen atom to zinc. This binding mode was, for the first time, characterized by X-ray structure analyses of the electrically neutral complexes [(Dpg-Phe)Zn], [(Dpg-Tyr)Zn], [(Dpg-Trp)Zn], and [(Dpg-Nal)Zn]. The pK values for amide nitrogen deprotonation were determined by H NMR titrations [(Dpg-Phe)Zn], 7.17; [(Dpg-Tyr)Zn], 6.85; [(Dpg-Trp)Zn], 6.85; [(Dpg-Nal)Zn], 6.64; [(Dpg-Gly)Zn], 8.54. It was calculated that aromatic interactions contribute ca. -8 to -11 kJ/mol of stabilizing free enthalpy changes in the derivatives with aromatic amino acid side chains. These are the first quantitative data obtained for crystallographically characterized metal complexes. A comparison with the literature shows that it is difficult to distinguish between π-cation attraction and π-π stacking. However, it is evident that modification of small peptides with synthetic pyridine ligands enhances their ability to stabilize secondary structures by noncovalent interactions. This is an important consideration for the design of biomimetic metallopeptides. © 2005 American Chemical Society.